The Effect of Using Vocabulary Journal Strategy on Students’ Reading Comprehension at State Junior High School 1 Cerenti Kuantan Regency - irma juita (Indonesian Journal of Integrated English Language Teaching, 2019)
This research was urged by the students’ problem in reading narrative texts at State Junior High School 1 Cerenti Kuantan Singingi Regency. For example, some students still had the difficulties in finding out the main idea and analyzing the reading text. Thus, the writer was interested in carrying out this research based the problems above. The objective of this research was to find out whether there was or nor  significant effect of using Vocabulary Journal strategy on students’ reading comprehension at State Junior High School 1 Cerenti Kuantan Singingi Regency.The design of this research was a quasi experimental design. The population of this research was the eighth grade students of Junior High School 1 Cerenti Kuantan Singingi Regency in 2015-2016 academic years. The sample was taken by using cluster random sampling. The sample was VIII 1 as an experimental class, and VIII 2 as control class. Thus, the number of sample from two classes was 54 students. To analyze the data, the writer adopted independent sample T-test formula by using SPSS 16.0 version. After analyzing the data, the writer found the result of t-observe was 2.03 < 5.386 > 2.72. Thus, the writer could conclude that there is a significant difference between the students taught by using and taught without using Vocabulary Journal strategy on students’ reading comprehension in narrative text at State Junior High School 1 Cerenti Kuantan Singingi Regency.